Imaging the spine. Issue 7 (July 2018) - Suresh, Priya; Wong, Jenn S.
Abstract: The spine is a complex structure composed of different tissues with a wide range of clinical pathologies. There are multiple imaging modalities available at our disposal to image the spine. This article will present several common pathologies and how different imaging modalities have their respective roles in clinching the right diagnosis and aiding subsequent management.